Drafts, fragments, and poems the complete poetry - Murray, Joan 1917-1942 (New York Review Books, 2017)
"The first appearance of this award-winning writer's work since the 1940s, this collection, which includes an introduction by John Ashbery, restores Joan Murray's striking poetry to its originally intended form. When John Ashbery hailed Joan Murray as a major influence in an essay in 2003, her sole collection Poems, had been out of print for decades. Joan Murray hit the literary scene as a bright talent in American poetry just before her death of a heart condition in 1942. She was only in her twenties. After her death, W.H. Auden selected Murray for the 1946 Yale Younger Poets Prize. As she left behind no definitive edition of her work, her Poems was compiled by Grant Code, a close friend of Murray's mother. Code heavily edited the manuscript, often streamlining Murray's raw lyricism, and left out dozens of poems. It had originally been supposed that Murray's original manuscripts had been lost, but a trove of her writings miraculously resurfaced in 2013. In Collected Poems, Farnoosh Fathi has gone through all of Murray's papers and reinstated her visionary lines, while also recovering much previously unpublished verse. An heir to W.B. Yeats, Walt Whitman, Hart Crane, and Laura Riding, Murray today, with her vatic lullabies and mythic imagination, still belongs to the future"--
Keywords: POETRY / American / General